Accounting for interspecific competition and age structure in demographic analyses of density dependence improves predictions of fluctuations in population size. (28th February 2019) - Gamelon, Marlène; Vriend, Stefan J. G.; Engen, Steinar; Adriaensen, Frank; Dhondt, André A.; Evans, Simon R.; Matthysen, Erik; Sheldon, Ben C.; Sæther, Bernt‐Erik
Abstract: Understanding species coexistence has long been a major goal of ecology. Coexistence theory for two competing species posits that intraspecific density dependence should be stronger than interspecific density dependence. Great tits and blue tits are two bird species that compete for food resources and nesting cavities. On the basis of long‐term monitoring of these two competing species at sites across Europe, combining observational and manipulative approaches, we show that the strength of density regulation is similar for both species, and that individuals have contrasting abilities to compete depending on their age. For great tits, density regulation is driven mainly by intraspecific competition. In contrast, for blue tits, interspecific competition contributes as much as intraspecific competition, consistent with asymmetric competition between the two species. In addition, including age‐specific effects of intra‐ and interspecific competition in density‐dependence models improves predictions of fluctuations in population size by up to three times.